Success Begets Success - Nero, Sean (Trinidad Guardian)
Success Stars Pan Sounds, joint Junior Steelband Music Festival winner, won new friends at the Aberdeen International Youth Festival in Scotland. The 24-member band was accompanied by four teachers, along with Cary Codrington (arranger), Egar Meyers (tuner) and musical director, Ben Jackson.
Keywords: Steel bands (Music) -- Scotland; Steel band music -- Scotland; Music and youth -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago